New armored spiders of the family Tetrablemmidae from China - Lin, Yucheng; Li, Shuqiang (Zootaxa, 2010)
Five new species of the family Tetrablemmidae, occurring in the southern China, are described and illustrated: i.e., Lehtinenia arcus sp. nov., Shearella sanya sp. nov. from tropical shrub in Hainan Island, and Indicoblemma cruxi sp. nov., Singaporemma bifurcata sp. nov., Tetrablemma nandan sp. nov. from caves of Yunnan-Guizhou Plateau. The genera Indicoblemma, Shearella and Singaporemma are reported in China for the first time. All type specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences, Beijing.